Chemical enrichment in the centers of clusters and groups of galaxies with cold cores observed with Suzaku - A. Dupke, Renato; M. Batalha, Rebeca; Jiménez-Teja, Yolanda (Cadernos de Astronomia, 2024)
This study investigates the distribution of the mass fraction of Iron (Fe) from Type II Supernovae (SNII) compared to Type Ia Supernovae (SNIa) in eighteen clusters and groups of galaxies with cold cores observed with Suzaku . Using the theoretical models of supernova explosions best evaluated by [1], we calculated this fraction from eight abundance ratios in the cold core regions and their external regions. The inner region demonstrates a smaller contribution of Fe mass fraction from SNII/SNIa compared to the outer region. The weighted average Fe mass fractions of SNII/SNIa, derived from the eight measured abundance ratios, increase from 17.0 ± 0.2 to 21.3 ± 0.6. This average increase indicates that the inner region has a higher percentage mass fraction of Fe originating from SNIa than in the outer region. Among the mechanisms of chemical enrichment in galaxy clusters and groups, this result suggests that the drag pressure in the central region of these galaxy clusters plays a crucial role in the chemical enrichment of these regions, corroborating previous findings.